Peru : Diagnostic Review of Consumer Protection and Financial Literacy - World Bank (Washington, DC, 2014)
The diagnostic review for consumer protection and financial literacy (CPFL) provides a detailed assessment of the institutional, legal, and regulatory framework for consumer protection in four segments of the financial. A World Bank (WB) mission visited Peru from March 18 to 27, 2013 to prepare the review. The objectives of the CPFL review were: (i) to assess the existing consumer protection and financial literacy framework by reviewing laws, regulations, and practices in Peru compared to international good practices; and (ii) to provide recommendations on ways to improve the level of financial consumer protection and financial literacy in Peru. It seeks to identify key measures in strengthening financial consumer protection, with the ultimate aim of increasing the availability and transparency of financial information, helping build consumers' trust in the financial sector, and expanding their capacity to wisely use financial services. The review addresses the following issues: (1) institutional arrangements, (2) legal and regulatory framework, (3) disclosure, (4) business practices, (5) dispute resolution mechanisms, and (6) financial education.